Religion in the Age of Social Distancing: How COVID-19 Presents New Directions for Research. (16th September 2020) - Baker, Joseph O; Martí, Gerardo; Braunstein, Ruth; Whitehead, Andrew L; Yukich, Grace
Abstract: In this brief note written during a global pandemic, we consider some of the important ways this historical moment is altering the religious landscape, aiming our investigative lens at how religious institutions, congregations, and individuals are affected by the social changes produced by COVID-19. This unprecedented time prompts scholars of religion to reflect on how to strategically approach the study of religion in the time of "social distancing, " as well as moving forward. Particularly important considerations include developing heuristic, innovative approaches for revealing ongoing changes to religion, as well as how religion continues to structure social life across a wide range of contexts, from the most intimate and personal to the most public and global. Although our note can only be indicative rather than exhaustive, we do suggest that the initial groundwork for reconsiderations might productively focus on several key analytical themes, including: Epidemiology, Ideology, Religious Practice, Religious Organizations and Institutions, as well as Epistemology and Methodology. In offering these considerations as a starting point, we remain aware (and hopeful) that inventive and unanticipated approaches will also emerge.